Hemoglobin Evaluation in Hypertensive Disorders of Pregnancy - Rabia Sattar; Ghazal Mansoor; Sana Qanber Abbasi; Qurat ul Ain; Sana Javaid; Nazish Jamil (Journal of the Dow University of Health Sciences, 2022)
Objective: To evaluate the maternal hemoglobin (Hb) concentration and its levels in hypertensive pregnant patients during the third trimester of gestation.